تأثير الرش بحمض الساليسيليك (Salicylic acid) في الصفات النوعية لدرنات البطاطا (Solanum tuberosum L.) صنف سبونتا - سليمان سوسن; زيدان رياض; خرماشو ديما (Latakia University Journal -Biological Sciences Series, 2018)
In this study, the effect of foliar spray with salicylic acid, on potato) Solanum tuberosum.L) Vr.Sponta on different concentrations of salicylic acid (0.05-0.1 -0.15 -0.2- 0.25-0.5 mM: SA) was investigated in the specific characteristics of potato tubers, in terms of percentage of starch, Soluble solids and their content of vitamin C and their content of nitrates and potassium. The results showed that the treatment of the different concentrations of SA significantly exceeded the treatment of the control in the content of tubers of dry matter and starch (especially in the treatment with 0.5mM concentration), reaching 26.58% and 18.01% respectively, and the percentage of vitamin C increased to 31.07% ) At the concentration (0.1 mM) was significantly higher than the control treatment (16.2%), but did not significantly affect the ratio of dissolved solids. The results also showed that spraying salicylic acid with different concentrations resulted in a decrease in the content of tubers of nitrate. The lowest concentration of nitrate was (0.5mM) (25.09ppm). The differences were significant between the salicylic acid and salicylic acid. Significantly in tubers (especially when treated with concentrations 0.1 - 0.2 - 0.25 mM), which contributes to obtaining better quality tubers. تم في هذا البحث دراسة تأثير رش أوراق نباتات البطاطا Solanum tuberosum (صنف سبونتا) بتراكيز مختلفة من حمض الساليسيليك ( mM 0.05 -0.1 -0.15 -0.2- 0.25- 0.5 SA) في الصفات النوعية لدرنات البطاطا، من حيث نسبة النشاء والمادة الجافة والمواد الصلبة الذائبة ومحتواها من فيتامين C و محتواها من النترات والبوتاسيوم. أظهرت النتائج أن المعاملة بالتراكيز المختلفة للـ SA تفوقت معنوياً على معاملة الشاهد في محتوى الدرنات من المادة الجافة والنشاء (خاصة عند المعاملة بالتركيز 0.5mM ) فبلغت النسبة (26.58%،18.01%) على التوالي، وكذلك قد ازادت نسبة فيتامين C فبلغت (31.07 %) عند المعاملة بالتركيز( 0.1 mM ) بزيادة معنوية مقارنة بمعاملة الشاهد (16.2%)، لكنها لم تؤثر بشكل معنوي في نسبة المواد الصلبة الذائبة. بينت النتائج أيضاً أن رش الأوراق بالتراكيز المختلفة لحمض الساليسيليك قد أدى إلى انخفاض محتوى الدرنات من النترات، وكانت أقل كمية من النترات عند التركيز( 0.5mM ) (25.09ppm ) وكانت الفروق معنوية بينها وبين معاملة الشاهد، أيضا ساهم حمض الساليسيليك في زيادة تركيز البوتاسيوم بشكل معنوي في الدرنات (خاصة عند المعاملة بالتراكيز 0.1 - 0.2- 0.25 mM)، مما يساهم في الحصول الدرنات نوعية أفضل.